2021
DOI: 10.1186/s12909-021-02521-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of remote online exam delivery on student experience and performance in applied knowledge tests

Abstract: Background The use of remote online delivery of summative assessments has been underexplored in medical education. Due to the COVID-19 pandemic, all end of year applied knowledge multiple choice question (MCQ) tests at one UK medical school were switched from on campus to remote assessments. Methods We conducted an online survey of student experience with remote exam delivery and compared test performance in remote versus invigilated campus-based f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
3
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 12 publications
4
42
3
7
Order By: Relevance
“…Multiple studies have shown that in non-proctored online exams, students seek assistance from friends or books, which underlines the need for some form of supervision during online summative tests [2,[8][9][10]. Previous studies have focused on test results and test anxiety in online assessment [3,4,11]. In an unproctored remote Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown that in non-proctored online exams, students seek assistance from friends or books, which underlines the need for some form of supervision during online summative tests [2,[8][9][10]. Previous studies have focused on test results and test anxiety in online assessment [3,4,11]. In an unproctored remote Fig.…”
Section: Discussionmentioning
confidence: 99%
“…examination setting [11], students' opinions were mixed: they either felt more at ease at home or reported higher test anxiety due to worries about unstable internet connection. Studies regarding students' perceptions of on campus versus online, remote exams reported more stress amongst students taking the exam remotely [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Esse perfil de resultado é semelhante a outros dados de literatura sobre o OSCE presencial, no qual mais de 75% dos estudantes entrevistados consideraram alto grau de ansiedade durante a avaliação, embora o método tenha sido considerado aplicável, abrangente, justo e transparente por estes alunos. (Jaap et al, 2021) Para que a realização do Web-OSCE seja satisfatória, é necessária uma série de fatores: equipe de suporte em tecnologia da informática, plano operacional, treinamento dos atores, inclusive para a utilização das ferramentas tecnológicas, acesso de internet adequado para todos os participantes, dispositivos com áudios/vídeos, sendo extremamente relevante o feedback de todos os envolvidos. Além de toda a implementação técnica, a validade das questões aplicadas é de extrema relevância, com adequado grau de dificuldade e compatível com o conteúdo pedagógico.…”
Section: Discussionunclassified
“…Até maio de 2021, 162.704.139 Ceará, 2020;Hodges, Moore, Lockee, Trust, & Bond, 2020) A pandemia causou não apenas uma transformação da educação quanto ao modo de ensinar, mas também quanto ao modo de avaliar a aprendizagem, tornando a situação mais complexa com a necessidade de adaptação para aplicação de avaliações de forma remota. (Jaap et al, 2021) Apesar de haver poucos estudos considerando os desafios da aplicação de avaliações remotas, no ensino médico, tornouse presente não somente a necessidade de adaptação para a aplicação de avaliações de conhecimento por meio de testes de múltipla escolha, mas também a de avaliar habilidades e atitudes frente a problemas pertinentes à prática médica. (Alruwais, Wills, & Wald, 2018) Existem vários métodos possíveis para avaliação prática de estudantes de medicina, incluindo métodos mais tradicionais e antigos -prova oral, short case e long case -criticados pela pouca padronização, confiabilidade e possível viés do avaliador; bem como existem modelos baseados em simulação como o Objective Structured Clinical Examination (OSCE), que garante a segurança do paciente e torna possível a avaliação de três domínios: cognitivo, afetivo e psicomotor.…”
Section: Introductionunclassified
“…Thus, the teacher should have knowledge of different types of evaluation (Compton, 2009) to choose the appropriate kind of technology that may be benefit (Chapelle, 2001). A study by Jaap, Dewar, Duncan, Karen, David, (2021) revealed that a most of students felt more nervousness during the e-examination because their concerns were related about technical issues. So, most students preferred the traditional examination compared to e-examination.Teachers should have a role of improving the learning process of the students.…”
Section: Evaluation and Assessment Skillsmentioning
confidence: 99%